Mucormycosis in diabetic patients post-COVID-19 infection - Elguera-Falcón, Federico (2020)
Mucormicosis is an infection caused by Mucorales fungi. Among the most common risk factors are uncontrolled and complicated diabetes mellitus with diabetic ketoacidosis, corticoid use, etc. Clinical characteristics depend on the type ofinvolvement, the most common being: fever, sinusitis, proptosis, headache, paralysis of cranial nerves, etc. Treatment consists of early antifungal therapy, early and extensive surgery, and proper management of comorbilities. The clinical picture of four decompensated diabetic patients who had rhino-orbit-brain mucormycosis following a COVID-19 infection is described.